Fabrication of a Custom Sectional Impression Tray for a Patient with Oral Submucous Fibrosis - Caculo, Shweta Pandurang; Aras, Meena Ajay; Chitre, Vidya (Journal of Orofacial Research, 2013)
Gaining access into the oral cavity of patients with limited mouth opening is difficult and rehabilitation of such patients is a challenge. The loaded impression tray is a bulky item that needs to be placed intraorally. In patients with microstomia, obtaining accurate impression using conventional techniques is difficult due to limited mouth opening and thus alternate clinical procedures need to be developed. This case report describes an innovative technique for fabrication of custom maxillary sectional tray for a patient with oral submucous fibrosis utilizing components that are commonly available, enhancing the comfort of both operator and the patient.